Responding the Crime of Running Away from Underage Girls: is Mediation the Right Solution - Achmad Arifulloh (Faculty of Law, Universitas Pekalongan, 2022)
The research was based on the large number of criminal cases of running away underage women that occurred in Demak Regency. This research aims to find out and understand the legal construction of the crime of running away from underage women, the factors that cause the crime of running away from underage women, and the process of resolving the crime of running away from underage women through mediation. The research method uses a juridical-sociological approach. The results of this research show that the legal construction of the criminal act of running away from underage girls according to the Criminal Code is regulated in Article 332 and Article 82-83 of Law Number 23 of 2002 concerning Child Protection as amended by Law Number 35 2014 concerning Child Protection and must have elements of the subject running away, the object being run away and the act of taking them away. And the factors that cause the crime of running away from underage girls are factors: 1) lack of social interaction, 2) economic factors, 3) parental attention factors, 4) educational factors, and 5) low religious knowledge and the process of resolving criminal acts. Escaping minors through mediation is carried out in the following stages: 1) Report/complaint reception stage, 2) Forum formation stage, 3) Problem deepening stage, 4) Final settlement stage and determining the results of the agreement, 5) Stage involving community leaders, and 6) Mediation ending stage.